If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3cos(x) + 1 = 3 Multiply cos * x 3cosx + 1 = 3 Reorder the terms: 1 + 3cosx = 3 Solving 1 + 3cosx = 3 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3cosx = 3 + -1 Combine like terms: 1 + -1 = 0 0 + 3cosx = 3 + -1 3cosx = 3 + -1 Combine like terms: 3 + -1 = 2 3cosx = 2 Divide each side by '3osx'. c = 0.6666666667o-1s-1x-1 Simplifying c = 0.6666666667o-1s-1x-1
| 4x-10+2x=2x-14 | | 9.9+m=4m-15 | | 2-(5x-22)=6(x-2) | | 114/8 | | 3x/12=3 | | (30-3X)X=0 | | 2x^2+31=-9 | | 8=5-3(x-4) | | -9n-6n=11(1+3n)-11(1+11n) | | .25-2y=11 | | -3x+2(x-4)=-3(x-8) | | 858/24 | | X^2-10-20=0 | | .25-2y=13 | | 11b+17-9b=41 | | -25/28*(-21) | | 1/4*7/6 | | 5x=9-16 | | 8x-112=64 | | V=3.14r^2(60-2r) | | 9/28*19/54 | | -2(9n-4)=2(11-8n) | | 2x^(2/3)-x^(1/3)=6 | | -4v+2=2(v+7) | | -8=2(x+6) | | 5x+3y=371 | | w+10=3w-10 | | 4(-5+7a)=26+5a | | 9/28•19/54 | | (14n/3)=8(n-14) | | -25/28•(-21) | | 2X-(5X+9)=8-3X |